Magainin analogs effective against pathogenic protozoa. - Huang, C M (1990)
The in vitro activities of magainin analogs against Blastocystis hominis, Entamoeba histolytica, and Trypanosoma cruzi were assessed by protozoan morphological integrity and motility. The antiprotozoan activities in descending order were magainin B greater than G greater than H, the same order as the alpha-helix contents of the analogs. Magainin B and G were effective against B. hominis, T. cruzi, and E. histolytica.